2015
DOI: 10.1007/s12665-015-4559-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration from China’s afforestation projects

Abstract: Since the late 1970s, the Chinese government has implemented massive afforestation projects to address grievous environmental disasters, protect human health and provide long-term environmental security. Having a better understanding of the total carbon sink from the afforestation projects is fundamental to assess its global carbon benefit. Here, the sequestered carbon stock based on Chinese national forest inventory data is calculated by using three comparable volume-derived biomass models. Results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…The GIMMS data are corrected for changes in satellite sensors over time, unstable atmosphere conditions, and noise from non-vegetated areas [ 31 33 ]. For these reasons, the data have been widely applied in ecosystems research [ 27 , 34 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The GIMMS data are corrected for changes in satellite sensors over time, unstable atmosphere conditions, and noise from non-vegetated areas [ 31 33 ]. For these reasons, the data have been widely applied in ecosystems research [ 27 , 34 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…This result demonstrates that human environmental construction has played a great role. However, it is worth noting that the main result of NPP increases in arable land is an improved food supply, not carbon sequestration [64][65][66][67]. Irrigation, long-term chemical fertilization, high-density cultivation and other measures may result in the degradation of soil conditions.…”
Section: Impact Mechanisms Of Anthropogenic Activities On Vegetation ...mentioning
confidence: 99%
“…The total loss of NPP due to replacing vegetation with urban land reached 0.137 Tg C in the Pearl River Delta during 2000–2010 (Jiang et al, 2015). In contrast, many researchers have suggested the effectiveness of ecological restoration programmes and demonstrated that returning cropland to forest and grassland has facilitated vegetation recovery and greening at different spatial scales, including the national scale (He, Miao, Cui, & Wu, 2015b) and within an ecologically fragile region, such as the Loess Plateau (Xie, Qin, Wang, & Chang, 2014; Zhao et al, 2017) and the Tibetan Plateau (Gao et al, 2013). Although numerous studies have been carried out to evaluate how land use changes affect NPP ranging from the regional to the national and global scales, there are relatively few studies on the effects of land use change on the trends of NPP, especially nonlinear trends, which cannot fully reflect the response of NPP to land use change.…”
Section: Introductionmentioning
confidence: 99%